Value : sources and readings on a key concept of the globalized world - De Gennaro, Ivo. (Studies on the Interaction of Art, Thought and Power, 2012)
\'Value\' is arguably one of the key concepts of the globalized world. In this world, to be is to be or have a value, while all thinking and implementing has the form of valuing and evaluating. Thanks to their operative expediency, both the concept of value and thinking through values appear as sufficient and such as not to need any interrogation as to their provenance and implications. The essays of this volume, on the other hand, provide insights precisely in these aspects by presenting, on the one hand, classical philosophical sources on value, and, on the other, readings that show how the concept of value shapes our manner of thinking in pivotal issues and domains of economics, culture and knowledge.